An explanatory study on the space utilization of the shared bedrooms in the Kalayaan Residence Hall through semiotics - Mendoza, Alyssa Jayne S.; Florendo, Raquel B. (Quezon City College of Home Economics, University of the Philippines Diliman, 2014)
ABSTRACT This explanatory case study with a multi-method approach was undertaken to investigate the semiotics in relation to the space utilization of personal spaces of the female residents of the shared bedrooms in the Kalayaan Residence Hall. This research aimed to determine how the residents utilize their bedroom in terms of their personalization and organization strategies. The meanings behind these practices were also analyzed. Data was gathered elicited from twenty (20) respondents who were non-purposively selected through a semi-structured questionnaire. Five (5) informants from the same pool of respondents were also interviewed. The bedroom space of the informant underwent site-observations and photo-documentation. Results show that the female residents of the Kalayaan Residence Hall utilize their bedroom in different ways unique to their personality and preferences. They personalize their space through revamping the furniture, displaying personal items, and keeping their personal items in the bedroom to enhance their mood, express their identity, and to capture the image of their home. On the other hand, they organize their bedroom through the arrangement of their belongings and maintenance, by allotting specific storage spaces for their belongings, and by the use of organizers. The study revealed that they organize their bedroom due to accessibility, productivity, adaptation, and the concept of ?hiya? purposes. Afters gathering and analyzing data, the researcher concluded that much can be learned about the user by the he or she utilizes or her space.
Thesis (B.S. Interior Design)--University of the Philippines Diliman, 2014.
Keywords: Bedrooms -- Philippines; Dormitories -- Philippines